Typing of Mycobacterium bovis in formalin-fixed, paraffin-embedded tissues from selected wildlife species in the Kruger National Park, South Africa - Venter, Estelle Hildegard (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.